Vinland saga. Book twelve - Yukimura, Makoto, 1976- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2021)
"Sigurd returns home to Iceland to face the horrible Halfdan, but a father and a king can only be as good as his word--a blessing he refuses to bestow to Sigurd without a fight. All the while, Gudrid joins Thor and the crew on their journey to Thor's childhood home, where Halfdan's presence looms mightily. However, with some help from fresh faces and promising volunteers, the day the ships set off for Vinland is imminent"--